Real Venture Capital Building International Businesses - Thompson, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
A principal theme of the book is a plea for ' real venture capital', with the venture capitalist adding substantial value to companies and their founders through a wide knowledge of business, in contrast to the purely financial skills required in other sectors of the private equity field, such as leveraged buy-outs.
Keywords: New business enterprises; Accounting; Bookkeeping .; International business enterprises; Economics; Management science; Finance; Start-Ups/Venture Capital; Accounting/Auditing.; International Business; Economics, general; Finance, general